Vedas : an introduction to Hinduism's sacred texts - Dalal, Roshen (Gurgaon: Penguin Random House, 2014)
Includes English translation of selected verses from four Vedas.
Includes bibliographical references (pages 401-410).
Also available as an e-book.
Keywords: Vedas -- Criticism, interpretation, etc; Vedas-Hinduism; Hinduism